1981
DOI: 10.1159/000241483
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic 3′,5′-Adenosine Monophosphate in Umbilical Cord Blood of the Newborn Infant: Relation to Fetal Stress and Plasma Catecholamines

Abstract: Cyclic 3′,5′-adenosine monophosphate (cyclic AMP) was analyzed in the venous blood of the mothers and in the umbilical vein and artery of the infant at birth. In general, higher cyclic AMP levels were found in the umbilical vein than in the artery which were similar to the maternal values. Asphyxia and vacuum extraction were associated with significantly higher cyclic AMP levels, while the concentration was lower after elective cesarean sections than after uncomplicated vertex deliveries. The cyclic AMP concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(15 reference statements)
1
5
1
Order By: Relevance
“…The group of neonates investigated in the latter study, however, was composed of a mixed population: the infants were born following different types of deliveries and were of vari able gestational age and birth weight. This may explain the discrepancy between our data and those of Bisto/etti et al [7], It should also be noted that in the present study, in contrast to others [6,7], we ascertained that the blood specimens were indeed obtained from the UA or UV (by assaying progester one concentration).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The group of neonates investigated in the latter study, however, was composed of a mixed population: the infants were born following different types of deliveries and were of vari able gestational age and birth weight. This may explain the discrepancy between our data and those of Bisto/etti et al [7], It should also be noted that in the present study, in contrast to others [6,7], we ascertained that the blood specimens were indeed obtained from the UA or UV (by assaying progester one concentration).…”
Section: Discussioncontrasting
confidence: 99%
“…The markedly increased UA cAMP plasma concentration at term relative to the concentration in MV, as well as the arteriove nous gradient of plasma cAMP level in the fetoplacental circulation, strongly suggest that the high cAMP levels in the cord blood originate mainly from the fetus. Our results are in agreement with the data of Yuen et al [6], but diverge from those of Bistoletti et al [7] who concluded that higher cAMP levels were found in the UV than in the UA. The group of neonates investigated in the latter study, however, was composed of a mixed population: the infants were born following different types of deliveries and were of vari able gestational age and birth weight.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The rise of MABP may be indicative of such an effect of vasopressin. In the interpre tation of changes found in the water perme ability and pinocytosis of brain micro vessels, the possible involvement of other vasoactive substances, such as histamine [13,14] and norepinephrine [42] as well as the cyclic AMP and cyclic GMP [8,27,28] should also be taken into consideration. The fact that potassium content did not change signifi cantly in hypoxic-hypercapnic conditions shows the high resistance and different meta bolic rate of neurons in the newborn piglets [2,19,54].…”
Section: Discussionmentioning
confidence: 99%
“…One important endogenous mechanism influencing FLL secretion and absorption is obviously the sympathetic nervous system [21] which increases markedly in activity during labor and parturition [3,13]. As men tioned previously (see Introduction) (3-adrenergic mechanisms seem to be of spe cific importance.…”
Section: Discussionmentioning
confidence: 73%